Assessing the importance of livestock water use in basins - Cook, Simon E.; Andersson, Meike S.; Fisher, Myles J. (Commonwealth Scientific and Industrial Research Organisation, 2009)
Recent concern over food prices has triggered a renewed interest in agricultural production systems. While attention is focused mainly on cropping, a complete analysis of food production systems should recognise the importance of livestock as major consumers of resources – in particular water – and as providers of food and other products and services. We propose that there is a need to examine not just food systems in isolation, but combined food and water systems, both of which are described as in a critical condition. From this broader perspective, it appears even more important to understand livestock systems because first, a total evaluation of agricultural water productivity – the gain from water consumed by agriculture – cannot be made without understanding the complexities of livestock-containing systems and; second, because in most tropical river basins, livestock systems are the major consumers of water. To identify total water productivity of livestock-containing systems, we describe concepts of agricultural water productivity and review the complexities of tracking the flow of water through livestock-containing systems: from inputs as evapotranspiration (ET) of forage and crops to outputs of valued animal products or services. For the second part, we present preliminary results from water use accounts analysis for several major river basins, which reveal that for Africa at least, livestock systems appear to be the major water consumers. Yet, little is known about the fate of water as it passes through these systems. We propose that livestock-containing systems offer substantial scope for increasing total water productivity and that there is considerable merit in improving the capacity to analyse water consumption and water productivity through such systems. Without removing this major source of uncertainty, the potential for systemic improvement to meet the world food and water crisis remains undefined and hence under-acknowledged.